Interactive data visualization for the web : an introduction to designing with D3 - Murray, Scott (College teacher) (Beijing ; Boston : O'Reilly, 2017)
Author Scott Murray teaches you the fundamental concepts and methods of D3, a JavaScript library that lets you express data visually in a web browser.
Introducing D3 -- Technology fundamentals -- Setup -- Data -- Drawing with data -- Scales -- Axes -- Updates, transitions, and motion -- Interactivity -- Using paths -- Selections -- Layouts -- Geomapping -- Exporting -- Project walk-through.
Includes bibliographical references (pages 413-416) and index.
Keywords: JavaScript (Computer program language) -- Handbooks, manuals, etc; Information visualization -- Data processing -- Handbooks, manuals, etc; Interactive computer graphics -- Handbooks, manuals, etc; Web-based user interfaces -- Handbooks, manuals, etc; Interactive computer graphics; JavaScript (Computer program language); Web-based user interfaces; Handbooks and manuals